A literacia em leitura - Fátima Sequeira (Universidade do Minho, 2002)
For the second time in a decade, Portugal presents poor results on reading literacy tests involving students of several countries. The tests tried to measure reading literacy as the ability to understand and use written forms required and valued by society. Portuguese students showed larger advantage on narrative texts mainly because Portuguese schools are more likely to train students on narrative comprehension. On the contrary, on documents and recognition domains Portuguese students scored poorly. It is time to give all the Portuguese children a head start in order to achieve acceptable levels of reading literacy by attending well-resourced schools, with libraries, textbooks and well trained teachers.